Siren songs: a novel sonification method for network traffic and intrusion detection - Skarth-Hayley, Luke (2017)
Live and retrospective analysis of network traffic is a challenging task in any busy IT Department or Network Operating Centre. Examining graphs and log files is time-consuming, and alerts can be missed. As an alternative to visual representations this research investigates sonification, turning network data and attack signatures into audio, specifically music, that provides an ‘at-a-listen’ state of the network that during normal operation is easy to ignore and non-fatiguing for listeners, and during attacks clearly surfaces the type of attack with a unique combination of musical instrument and phrase. Prior research has been carried out into network sonification, but reviews of the field reveal a lack of musicality and formal grammar in these sonifications, something this project seeks to redress. A series of prototypes are presented, leading to a flexible system where users can define their own musical phrases to represent network conditions and potential intrusions, from which future research could be made, examining the efficacy of various forms of musical sonification.